The link between brand reputation risk and outdoor road advertising. - Masuku, Freeman Nkululeko (My University, 2017)
Brand reputational problems are legion and in the age of the rise of social media and easier access to information, management of brand reputation risk is becoming increasingly critical especially in outdoor advertising where problems can easily go viral. Outdoor roadside advertising has played a critical role in the past century in building and supporting organisations’ brands, identity and reputation and forms a critical component of marketing strategies. However, there are issues in outdoor advertising, particularly public safety on South Africa’s roads. Issues of public safety could potentially damage brands and therefore it is critical to manage brand reputation risk in outdoor advertising. Potential reputational problems to a brand comes in many forms and from many stakeholders, but not all problems affect the essence of a brand. In all instances, organisations must be able to identify and manage risks to the brand, in particular, those emanating from corporate communication strategies. A number of researchers have confirmed that outdoor roadside advertising can cause accidents on roads, although there are no studies that have been done in South African conditions. The essence of outdoor advertising as an attention grabbing distraction likely to cause road accidents, warrants attention. This study assessed the link between potential brand reputational risk and issues concerning outdoor roadside advertising, with the aim of determining the level of awareness amongst marketing professionals in South Africa regarding this issue. It found that there is a link between brand reputational risks, potential brand crisis and problems associated with roadside advertising particularly accidents, and that marketing professionals are not aware of the risks to motorists associated with outdoor roadside advertising. The study was exploratory in nature and the data was collected through semistructured interviews with a purposefully selected sample of experts. The data was analysed using direct content analysis. The research found that there is potential link between brand reputational risk and road safety issues. However, the study is inconclusive in terms of what effect heightened awareness would have on marketing strategies particularly the choice of where advertising signs should be placed.
MBA Thesis
Keywords: Advertising, Outdoor,Brand name products,Social media -- South Africa.